The influence of maturation on exercise‐induced cardiac remodelling and haematological adaptation - Perkins, Dean R.; Talbot, Jack S.; Lord, Rachel N.; Dawkins, Tony G.; Baggish, Aaron L.; Zaidi, Abbas; Uzun, Orhan; Mackintosh, Kelly A.; McNarry, Melitta A.; Cooper, Stephen‐Mark; Lloyd, Rhodri S.; Oliver, Jon L.; et al. (The Journal of physiology, 2022)
Cardiovascular and haematological adaptations to endurance training facilitate greater maximal oxygen consumption (V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$), and such adaptations may be augmented following puberty. Therefore, we compared left ventricular (LV) morphology (echocardiography), blood volume, haemoglobin (Hb) mass (CO rebreathing) and V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ in endurance‐trained and untrained boys (n = 42, age = 9.0–17.1 years, V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ = 61.6 ± 7.2 ml/kg/min, and n = 31, age = 8.0–17.7 years, V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ = 46.5 ± 6.1 ml/kg/min, respectively) and girls (n = 45, age = 8.2–17.0 years, V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ = 51.4 ± 5.7 ml/kg/min, and n = 36, age = 8.0–17.6 years, V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ = 39.8 ± 5.7 ml/kg/min, respectively). Pubertal stage was estimated via maturity offset, with participants classified as pre‐ or post‐peak height velocity (PHV). Pre‐PHV, only a larger LV end‐diastolic volume/lean body mass (EDV/LBM) for trained boys (+0.28 ml/kg LBM, P = 0.007) and a higher Hb mass/LBM for trained girls (+1.65 g/kg LBM, P = 0.007) were evident compared to untrained controls. Post‐PHV, LV mass/LBM (boys: +0.50 g/kg LBM, P = 0.0003; girls: +0.35 g/kg LBM, P = 0.003), EDV/LBM (boys: +0.35 ml/kg LBM, P < 0.0001; girls: +0.31 ml/kg LBM, P = 0.0004), blood volume/LBM (boys: +12.47 ml/kg LBM, P = 0.004; girls: +13.48 ml/kg LBM, P = 0.0002.) and Hb mass/LBM (boys: +1.29 g/kg LBM, P = 0.015; girls: +1.47 g/kg LBM, P = 0.002) were all greater in trained versus untrained groups. Pre‐PHV, EDV (R2adj = 0.224, P = 0.001) in boys, and Hb mass and interventricular septal thickness (R2adj = 0.317, P = 0.002) in girls partially accounted for the variance in V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$. Post‐PHV, stronger predictive models were evident via the inclusion of LV wall thickness and EDV in boys (R2adj = 0.608, P < 0.0001), and posterior wall thickness and Hb mass in girls (R2adj = 0.490, P < 0.0001). In conclusion, cardiovascular adaptation to exercise training is more pronounced post‐PHV, with evidence for a greater role of central components for oxygen delivery. Key points It has long been hypothesised that cardiovascular adaptation to endurance training is augmented following puberty. We investigated whether differences in cardiac and haematological variables exist, and to what extent, between endurance‐trained versus untrained, pre‐ and post‐peak height velocity (PHV) children, and how these central factors relate to maximal oxygen consumption. Using echocardiography to quantify left ventricular (LV) morphology and carbon monoxide rebreathing to determine blood volume and haemoglobin mass, we identified that training‐related differences in LV morphology are evident in pre‐PHV children, with haematological differences also observed between pre‐PHV girls. However, the breadth and magnitude of cardiovascular remodelling was more pronounced post‐PHV. Cardiac and haematological measures provide significant predictive models for maximal oxygen consumption (V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$) in children that are much stronger post‐PHV, suggesting that other important determinants within the oxygen transport chain could account for the majority of variance in V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ before puberty. figure legend Schematic diagram depicting cardiac structural and haematological differences between trained and untrained boys and girls, pre‐peak height velocity (PHV) and post‐PHV alongside cardiac and haematological variables contributions to the variance in V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$. Cardiac and haematological variables are greater in trained versus untrained pre‐pubertal children, and a greater number and magnitude of differences are observed post‐PHV. These variables provide significant predictive models for maximal oxygen consumption in children and are much stronger post‐PHV, suggesting that other important determinants within the oxygen transport chain could account for the majority of variance in V̇O2max${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}$ before puberty.